The Impact of Candlestick Patterns and Stochastic Oscillator on Investment Interest in PT Akasha Wira Internasional Tbk's Stocks - Neni Prawira, Siti Amelia (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
The Indonesian capital market has experienced significant growth, marked by increasing retail investor participation—especially during the pandemic. Amid these dynamics, technical analysis has become a popular approach to investment decision-making, as it provides market signals based on historical price data. This study aims to analyze the impact of two technical indicators, Candlestick Charts and Stochastic Oscillator, on stock investment interest, with a case study on PT Akasha Wira Internasional Tbk listed on the Indonesia Stock Exchange. Using a descriptive quantitative approach, data were collected via questionnaires distributed to 50 retail investors and analyzed through multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results indicate that both Candlestick Charts and Stochastic Oscillator have a positive and significant influence on investment interest, both partially and simultaneously. The Candlestick variable yielded a significance value of 0.042, while the Stochastic Oscillator demonstrated a stronger effect with significance < 0.001. Together, these indicators explain 44.7% of the variation in investment interest (*R² = 0.447*). These findings suggest that technical indicators can enhance investor confidence and attractiveness in making investment decisions. The study recommends improving retail investor education on technical analysis to promote literacy and rational, analysis-based investment participation.